A Bibliometric Review of Research Trends on Digital Modules for Literacy and Numeracy in Elementary Schools - Laely Farokhah; Muhammad Zulfadhli; Dwi Novia Al Husaeni (Universitas Negeri Surabaya, 2025)
Research on digital modules to strengthen literacy and numeracy in elementary schools has increased in line with the growing need for technology-based instructional resources that are practical and have measurable impacts. This study aims to map publication trends, identify the most influential documents, and reveal the thematic structure of digital-module research on literacy and numeracy over the past decade. A bibliometric review was conducted using data retrieved from Google Scholar via Publish or Perish for the 2016–2026 period, applying an integrated keyword string and yielding 870 documents. The analysis includes descriptive statistics of annual publication trends, citation metrics to identify influential works, and thematic mapping through keyword co-occurrence and network visualization in VOSviewer, supported by data cleaning in RStudio. The results show a sharp increase in publications from 2021, peaking in 2025, while 2026 likely reflects partial-year indexing. The co-occurrence analysis (minimum occurrence = 10; 59 terms) produced six clusters dominated by the development–e-module theme and quality evaluation, with problem solving, ethnomathematics, and STEM integration emerging as key thematic strands. Overall, the field is shifting from artifact development toward stronger evidence of quality and learning impact. These findings inform a future research agenda emphasizing cross-context replication and provide guidance for evidence-based design and implementation of digital modules in elementary education.